Academic Resilience of Students in The Limited Face to Face Learning Period (PTM-T) - Dinda Putri Ramadhani; Dony Darma Sagita (Yayasan Keluarga Guru Mandiri, 2022)
Academic resilience is the ability of students to manage negative experiences that suppress the student's learning process by maximizing their potential to become resilient students and have good academic performance with all obstacles and social problems. The purpose of this study was to obtain the results of the academic resilience of SMA Muhammadiyah 2 Sidoarjo students during the Limited Face-to-Face Learning Period (PTM-T). This article measures the resilience level of students with the dimensions of resilience. The research instrument was adapted from the Indonesian Version of the Adaptation Factor Analysis of Academic Resilience Instruments: Exploratory and Confirmatory Approaches using quantitative methods. The sample used was 304 students of SMA Muhammadiyah 2 Sidoarjo. The analysis technique used is descriptive. The results showed that the average level of resilience of SMA Muhammadiyah 2 Sidoarjo students was 103.31 which could be interpreted in the high category. A total of 15 students with a percentage of 4.9% in the medium category and as many as 289 students with a percentage of 95.1% in the high category. This shows that with Limited Face-to-face Learning, students are still able to rise from academic difficulties that can hinder their learning process first during the current Limited Face-to-face Learning (PTM-T) period.